BIM in Kenyan construction industry: Benefits, challenges, and adoption processes in sustainable construction projects - Alakhali, Ahmed K.; Baarimah, Abdullah O.; Hasan, Kamrul; Halaba, Wail H.; Balfaqih, Ahmed S.; Mushtaha, Ahmed W. (IEEE, 2024)
The construction industry converts a wide range of resources into economic, social, and environmental infrastructure. Kenya's construction industry is emerging as a primary engine of economic expansion, accounting for 7% of the country's gross domestic product. Building Information Modeling (BIM) has become a nascent technology and method in the construction sector of Kenya. Globally, the construction sector is transitioning from conventional CAD to BIM. BIM adoption is accelerating globally, fueled by large private and public sector owners seeking to institutionalize its benefits. Consequently, it is important to know the challenges to BIM adoption and the processes of delivering BIM in the construction industry of Kenya. This study aims to examine the benefits of using BIM, determine its barriers, and formulate the processes for enhancing BIM adoption in the delivery of projects in the Nairobi construction industry. The methodology of this study used quantitative methods and the targeted are contractors' firms in Nairobi. Using the collection of 66 valid questionnaires from 125 C1 contractors, several statistical analyses were performed. The study demonstrated the substantial benefits of utilizing BIM in the Nairobi construction industry. However, there was consensus about the challenges of BIM adoption in the Nairobi construction industry faced by contractors. Furthermore, most of the respondents concurred with the suggested processes for enhancing the adoption of BIM in the delivery of sustainable construction projects in Nairobi city. Therefore, the research identified the significant benefits of BIM usage, challenges, and adoption processes in Kenya's sustainable construction practices.